Hadiths About Eating Hyena Meat in the Sunnah of the Prophet, A Critical Modern Study (Islamic Sciences Journal, 2023)
ABSTRACT              The science of the Prophet’s hadith is one of the most honorable legal sciences, as it is the second revelation after the Noble Qur’an, and the eminent scholars have been interested in everything that would clarify the correct hadith from its bad ones, because of that of a great impact in distinguishing the permissible and the forbidden, The researcher in such science cannot reach to the result closest to the truth except after exhausting the capacity to collect the methods from the various hadith sources, and to know the conditions of men, and to stand on the sayings of the scientist. I have studied in this study the hadiths about eating Hyena meat in the Sunnah of the prophet as a modern critical study in order to know the accurate hadiths which have not yet assured, and without referring to the juris prudential aspect this research. This research includes two topics, the first in the hadiths of the permissibility of eating, and the second in the hadiths that forbid eating.